Development of Halal Food for Health: Ready to Eat Chao Kuai in Goat Milk - ตาเย๊ะ, นุชเนตร; กุณฑล, นิภาภัทร์; โตะลู, มารีนี; โมงหนิมะ, นูรซาลีฮา (Princess of Naradhiwas University Journal, 2018)
The objective of this study was to develop a mixture of goat milk with Chao Kuai (grass jelly) from different providers and investigate: 1) quality of Chao Kuai production in local market, 2) quantity of fish gelatin added in Chao Kuai to define a standard formula, and 3) quantity of sugar in sweetened formula with pasteurized goat milk. The result indicated that an addition of 1% fish gelatin in Chao Kuai received the highest sensory evaluation score of overall liking (7.65±0.12 points). More gelatin resulted in less water release from gel in Chao Kuai and, therefore, a longer storage time (p<0.05). Addition of 12% sugar content in goat milk received the highest sensory evaluation score of odor and taste as 7.60±0.66 and 7.55±0.77 points with statistically significant (p<0.05). Chao Kuai in goat milk included protein, fat, carbohydrate, ash, fiber and moisture as 0.17%±0.13 0.02%±0.15 45.62%±0.21 10.20%±0.34 0.03%±0.10 and 43.96±0.42, respectively. The analysis of protein, fat, lactose and total solid in goat milk pasteurized was shown as 3.30±0.05, 3.68±0.10, 6.47±0.06 and 12.15±0.08, respectively that met the Thai Industrial standard (TIS: ICS 67.10.10). The shelf life of products determined by growth on general TPC, yeast and mold, as well as E.coli was stored for 8 days at 5±1°C. Those microorganisms did not exceed the standard.